Prediction of plastic instability in sheet metal forming using finite element method - José Manuel de Almeida César de Sá (2008)
The introduction of new materials brought new challenges to sheet metal forming processes. Theoptimization of these processes by using numerical simulations has become a key factor to acontinuously increasing requirement for time and cost efficiency, for quality improvement andmaterials saving, in many manufacturing areas such as automotive, aerospace, building, packagingand electronic industries. The behaviour observed with conventional steels may not be appliedwhen using high-strength steels or aluminium alloys. Numerical codes need to model correctly thematerial and different constitutive equations must be considered to describe with greater accuracyits behaviour. This enhancement of material description may provide a better prediction of theforming limits, enabling an assessment of the influence of each forming parameter on the neckingoccurrence and the improvement of press performance. This paper presents two numericalapproaches for failure prediction in sheet metal forming operations: one is the traditional use ofFLDs, usually employed as an analysis of the finite element solution in which the neckingphenomenon is carried out in the framework of Marciniak-Kuczynski (M-K) analysis coupled withthe conventional theory of plasticity and the other is the implementation of a ductile damagemodel in a commercial code in accordance with the theory of Continuum Damage Mechanics. Theprevious strategies and corresponding results are compared with experimental failure cases, inorder to test and validate each of these strategies.